Resistance Through Repurposing: An Analysis of Xenofeminism and the Evolution of Feminist Technologies (Groundings Undergraduate, 2024)
This paper provides a historical overview of the contemporary philosophy of Xenofeminism, and assesses how it theorises the intersections between feminism, technology, and futurity. By approaching 21st century feminist theory through the central tool of ‘repurposing’, Xenofeminism is established through its ability to adapt past feminist ideology for use in the present day. This paper will firstly evaluate how technologies developed as part of second wave feminism and ideologies of 1990’s cyberfeminism can be seen as key precursors to Xenofeminism; the paper will also consider the value and adaptability of past movements for contemporary notions of feminism as an intersectional practice. An overview of the three central lines of enquiry of Xenofeminism – ‘techno-materialism’, ‘anti-naturalism’ and ‘gender abolition’ – shall be situated within Helen Hester’s indispensable and explanatory text, Xenofeminism (2018). Ultimately this paper will contribute to the slowly emerging academic enquiry into Xenofeminism, identifying it as a productive and inclusive philosophy which remains grounded to the prevailing enquiry into the potential technology has to liberate women from systems of oppression.
Keywords: Xenofeminism; Women's Studies; Abortion rights; Women's rights; Protest; Cyberfeminism; Techno-materialism